Association of air quality with respiratory and cardiovascular morbidity rate in Delhi, India. - Maji, Sanjoy; Ghosh, Santu; Ahmed, Sirajuddin (International Journal of Environmental Health Research, 2018)
The present study reports short-term impact of poor air quality on cardiovascular and respiratory morbidity rate in Delhi. The data on monthly count of patients visiting Out Patient Department (OPD) and hospital admission due to respiratory and cardiovascular illnesses from hospitals along with daily air quality data from air quality monitoring stations of Central Pollution Control Board (CPCB), Government of India, across Delhi were collected for the period 2008 to 2012. A semi-parametric Quasi-Poisson regression model was used to examine the association of high pollution episodes with relative risk of hospital OPD visit and hospital admission due to respiratory and cardiovascular diseases. This study has confirmed the substantial adverse health effects due to air pollution across criterion air pollutants. The study reports the short-term effects of air pollution on morbidity from a time-series study first time in India. The study findings illustrate the evidence of adverse health impact of air pollution from India to the global pool and can influence the policy makers to implement better air quality management system for Indian cities. Abbreviations: OPD: Out Patient Department; IPD: Inpatient Department; RD: Respiratory Disease; CVD: Cardiovascular Disease; COPD: Chronic Obstructive Pulmonary Disease; CPCB: Central Pollution Control Board; NAAQMP: National Ambient Air Quality Monitoring Programme; NAAQS: National Ambient Air Quality Standards; RR; Relative Risk; IMD: Indian Meteorological Department; PM10: Particulate Matter less than 10 μm in aerodynamic diameter; SO2: Sulphur dioxide; NO2: Nitrogen dioxide; CO: Carbon Monoxide; O3: Ozone; DCE: Delhi College of Engineering; GTB Hospital: Guru Teg Bahadur Hospital; VPCH: Vallabhbhai Patel Chest Hospital; RMLH: Ram Manohar Lohia Hospital; SJH: Safdarjung Hospital; LNJPH: Lok Narayan Jai Prakash Hospital; GTBH: Guru Teg Bahadur Hospital; AH: Ambedkar Hospital; HRH: Hindu Rao Hospital; ESIH: ESI Hospital; SGRH: Sir Ganga Ram Hospital